(untitled) (Journal of Nepal Geological Society, 2001)
Small-amplitude lake-level fluctuations have been recognized from the aggrading delta-plain deposits in the lower parts of the Thimi and Gokarna formations, Kathmandu Valley, Nepal. The delta-plain deposits consist or gravelly sand beds of fluvial channel origin (coarse-sediment interval) and alternation of’ fine to very line sand and sandy silt beds (line-sediment interval). Wave generated structures occur in the sand beds or the fine sediment intervals. The vertical and lateral facies changes suggest that the deposition or a set of coarse- and fine-sediment intervals associated with prograding delta front deposits was controlled by a lake-level rise and fall sequence superimposed on a long-term lake level rise trend. The aggradation of fluvial sediments occurred during a lake-level rise period with sufficient sediment supply to fill a newly created accommodation space on the delta plain. The observation or wave-generated structures in an overlying fine-sediment interval suggests that the delta plain was subsequently inundated due to further lake-level rise, exceeding the sedimentation rate. Subsequent delta progradation occurred during a lake-level stabilized phase after a lake level fall. The small-amplitude lake-level changes are thought to be attribute able to seasonal wet and dry cycles, as inferred based on the presence of peculiar aggrading delta successions, implying that lake-level fluctuations may have occurred over short time scales, and on the results of a previous palaeopalynological study in which a moist palacoclimate was inferred in the lower part of the Gokarna Formation in particular.